Kontribusi Manajemen Sumber Daya Manusia Strategik Terhadap Kinerja PKL Implikasinya Terhadap Pendapatan Asli Daerah (PAD) Di Kota Probolinggo - HR. Abdul Haris (Fakultas Ekonomi Universitas Panca Marga, 2018)
This research was made using a combination of descriptive research and research using question narratives. Descriptive research is used to describe the strategic elements of Human Resource Management and the perspective of causality relationships from the Balanced Score Card. With the variables studied are: (1) Strategic Human Resource Management, (2) Performance with the Balanced Score Card method including financial perspective, customer perspective, internal business process perspective, and learning and growth perspective, (3) PKL contribution to income local government. The analysis used is line analysis and the results of the analysis show that: (1) Strategic Human Resource Management does not have a direct influence on Regional Government Revenues; However, it has an indirect influence on local government revenues through performance despite negative effects, (2) PKL performance has a negative direct influence on Local Government Revenues, (3) PKL elements, namely integration with PKL strategies has a direct influence on Revenue The Regional Government, indirectly, the long-term focus and growth of street vendors have a dominant direct influence on the revenue of the Regional Government through integration with the PKL strategy, (4) The focus on choice and decision making has a direct influence on the performance of street vendors. The biggest indirect effect is the influence of street vendor growth through a focus on choice and decision making, (5) The customer perspective has a direct influence on the revenue of the Regional Government despite negative influences. Another perspective from the Balanced Score Card, namely the customer perspective, internal business process perspective, and learning and growth perspective has an indirect influence on Local Government Revenues through a financial perspective. Keywords: Strategic Human Resource Management, Balanced Score Card Performance, Local Government Revenue